2011
DOI: 10.4103/0970-9290.79989
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and socio-demographic correlates of dental anxiety among a group of adult patients attending a dental institution in Vadodara city, Gujarat, India

Abstract: The study shows that dental anxiety was high among study subjects. It is recommended that this issue should be given due importance and addressed in a practical and meaningful manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

21
72
2
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(101 citation statements)
references
References 0 publications
21
72
2
6
Order By: Relevance
“…Locker and Liddell suggested that the age dependent decline in dental anxiety might be due to the general decline in anxiety with aging and greater exposure to other diseases and their treatment (27). Females in this study were more dentally anxious than males, similar to the findings of Acharya (22), Ekta A Malvania (32), and Vela D Desai (33) in the Indian population. Females are more likely to acknowledge their anxiety and are more prone to anxiety disorders (19).…”
Section: Discussionsupporting
confidence: 82%
“…Locker and Liddell suggested that the age dependent decline in dental anxiety might be due to the general decline in anxiety with aging and greater exposure to other diseases and their treatment (27). Females in this study were more dentally anxious than males, similar to the findings of Acharya (22), Ekta A Malvania (32), and Vela D Desai (33) in the Indian population. Females are more likely to acknowledge their anxiety and are more prone to anxiety disorders (19).…”
Section: Discussionsupporting
confidence: 82%
“…The prevalence of exacerbated dental anxiety is consistent with what was observed in England (McGrath & Bedi, 2004), India (Malvania &Ajithkrishnan, 2011) andBrazil (Maniglia-Ferreira et al, 2004;Rosa & Ferreira, 1997).…”
Section: Discussionsupporting
confidence: 76%
“…Often, in the literature, studies relate dental anxiety to gender (Garip, Abalı, Göker, Göktürk, & Garip, 2004;Hu et al, 2007;Kanegane, Penha, Borsatti, & Rocha, 2003;Malvania & Ajithkrishnan, 2011;Muglali & Komerik, 2008;Quteish Taani, 2002;Rosa & Ferreira, 1997;Schuller, Willumsen, & Holst, 2003;Settineri, Tati, & Fanara, 2005;Singh, de Moraes, & Ambrosano, 2000;Udoye et al, 2005), age (Malvania & Ajithkrishnan, 2011;Thomson, Stewart, Carter, & Spencer, 1996;Yuan et al, 2008) and educational levels (Chaves et al, 2006;Malvania & Ajithkrishnan, 2011;Maniglia-Ferreira et al, 2004;Rosa & Ferreira, 1997), however, in this study's sample these characteristics were not good predictors of dental anxiety (Figure 1). Thus, other variables should be considered in the model and, for that, exploratory studies should be initially performed, in order to identify the specific social and/or behavioural characteristics that may be related to the theoretical construct of anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sociodemographic factors have previously been established as risk factors for dental caries. 18 Like in another Indian study, 19 only 45% of the participants had ever visited a dentist. The participants who had visited the dentist before were asked about the frequency of their dental visit.…”
Section: Discussionmentioning
confidence: 99%